2020
DOI: 10.1080/09744053.2020.1755093
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the ‘Zimbabwean crisis 2000–2008’ and the survival strategies: the sustainable livelihoods framework (SLF) analysis

Abstract: In this paper, the author applies the Sustainable Livelihood Framework (SLF) to unravel the complexities inherent in the ‘Zimbabwean Crisis’. When unravelled from the SLF, the ‘Zimbabwean Crisis 2000-2008’ portrays a decimation of various forms of capital–financial, social, human, physical and natural–and forced Zimbabweans to innovate, show resourcefulness and ingenuity in generating various forms of capital to survive the scathing crisis. Broadly, the kukiya kiya strategy has received little scholarly study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In the post 2000 period Zimbabwe witnessed economic problems of significant proportion (Kabonga, 2020a). In summary, in the period between 2000 and 2008, the economy of Zimbabwe experienced worsening decline which, according to Kabonga (2020a), was characterised by shortages of foreign currency and spiralling hyperinflation, which triggered unemployment. At the same time employment in the agricultural sector was upset by the Fast Track Land Reform Programme which further exacerbated unemployment levels (Kabonga, 2020b).…”
Section: Informality Of the Informal Sector: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In the post 2000 period Zimbabwe witnessed economic problems of significant proportion (Kabonga, 2020a). In summary, in the period between 2000 and 2008, the economy of Zimbabwe experienced worsening decline which, according to Kabonga (2020a), was characterised by shortages of foreign currency and spiralling hyperinflation, which triggered unemployment. At the same time employment in the agricultural sector was upset by the Fast Track Land Reform Programme which further exacerbated unemployment levels (Kabonga, 2020b).…”
Section: Informality Of the Informal Sector: Contextmentioning
confidence: 99%
“…Studies in a different environment by Kanchana et al (2013) indicated that for young business people to be on a successful trajectory, they ought to manage risks and deal with an avalanche of challenges that come with running such businesses. Bindura, an agricultural and mining town, just like elsewhere in Zimbabwe, has, since the onset of the macroeconomic turmoil in 2000 (Kabonga, 2020a), witnessed the deterioration of the formal business sector while informal small businesses sprouted all over the town. In our case study area, the aforementioned economic crisis of the post 2000 period negatively affected the viability of mines such as Bindura Nickel, Trojan Nickel and Freda Rebecca gold mines.…”
Section: Introductionmentioning
confidence: 99%
“…Natural capital comprises of tangibles and intangible goods, such as air quality, soil quality and lodging for a healthy atmosphere (Campbell et al, 2002;Chapman et al, 2003;Erenstein et al, 2010). The SLF framework describes conditions which govern an individual's access to possessions and livelihood opportunities which can be converted into sustainable rural livelihood outcomes thus driving individuals out of the deprivation trap of poverty (Kabonga, 2020;Othman et al, 2016). Knutsson (2006) posited that the sustainable livelihoods outcome consists of five indicators which are more income, increased well-being, reduced vulnerability, improved food security and more sustainable use of natural resources.…”
Section: Sustainable Livelihoods Framework (Slf)mentioning
confidence: 99%
“…The SLF assumes that people live within a vulnerability environment made up of shock waves, developments and seasonality (Chitongo, 2019;Kabonga, 2020). The vulnerability environment is determined by converting structures and methods which include levels of government regulations, rules and culture that govern the livelihood strategies (Tabares et al, 2022;Kabonga, 2020) people use to meet their desired livelihood outcomes such as food security.…”
Section: Sustainable Livelihoods Framework (Slf)mentioning
confidence: 99%
“…Unemployment is a reflection of broader economic challenges of Zimbabwe. The Zimbabwean economy is yet to recover from the crisis period whose climax was the year 2008 (Kabonga, 2020). Socially, the interlocking economic challenges culminates in poverty.…”
Section: Introduction and Contextmentioning
confidence: 99%